The Unity of the Bible - Wright, G. Ernest (Scottish journal of theology, 1955)
The question of the unity of the Bible's message is one that will never be satisfactorily solved, though it is one which every generation of Christians must seek to solve. We are continually impelled to search for the answer because the unity of the Church's message to the world is at stake.